Clinical Evaluation of Respiratory-triggered 3D Magnetic Resonance Cholangiopancreatography with Navigator Echoes Compared to Breath-hold Acquisition Using Compressed Sensing and/or Parallel Imaging - Bhagwan Das, Pirya Nangdev, Kailash Kumar Daseja, Shaiq Hussain, Sushma Qadir, Aneel Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate image quality of respiratory triggered 3D MRCP with compressed parallel and sensing imaging in clinical setting. Study design: Cross-sectional study Duration and place of study: Study was conducted in the duration of1st July 2021 to 31st December 2021 at Department of Radiology, Chandka Medical College Hospital, Larkana. Methodology: Ninety patients with age between 40-70 years were enrolled. The patients got three various kinds of MRCP 3 dimensional as a protocol of their diagnosis plan. Four point scoring system was adapted for quality assessment. Results: The mean age of the patients was 66.9±8.6 years. There were almost similar number of males and females. Minimally invasive-intraductal papillarymucinous carcinoma was presented only in 2.22%. Comparison of three magnetic resonance cholangiopancreatography techniques showed that signal quality, was better as longer time involved in 1st magnetic resonance cholangiopancreatography case while blurring was also seen in breath holding magnetic resonance cholangiopancreatography. Conclusion: Better imaging quality of ductal system is obtained through respiratory triggered 3D magnetic resonance cholangiopancreatography against breath hold. Keywords: Magnetic resonance cholangiopancreatography, 3D Imaging, Compressed Sensing, Parallel imaging